Role of cannabidiolic acid or the combination of cannabigerol/cannabidiol in pain modulation and welfare improvement in horses with chronic osteoarthritis - Aragona, Francesca; Tabbì, Marco; Gugliandolo, Enrico; Giannetto, Claudia; D’Angelo, Fabiola; Fazio, Francesco; Interlandi, Claudia (Frontiers in Veterinary Science, 2024)
Cannabidiol (CBD) is a non-psychotropic cannabinoid obtained from hemp (Cannabis sativa L.) used for pain management in companion animals including horses. The present study aimed to evaluate the efficacy of cannabidiolic acid (CBDA) and cannabigerol/cannabidiol oil (CBG/CBD) oral administration in alleviating pain in adult horses affected by chronic osteoarthritis (OA). Twenty-four horses (10 geldings and 14 mares), aged between 11 and 18 years old, were equally divided into two groups. One group received CBDA 15% oil and the other group received CBG/CBD oil (CBG20%-CBD10%) for 14 consecutive days. A standard dose of 0.07 mg/kg was chosen based on the mean body weight of 450 ± 28 kg. Horse Chronic Pain Scale (HCPS) and physiological parameters monitoring heart rate (HR), respiratory rate (RR), arterial blood pressure (systolic arterial pressure- SAP, diastolic arterial pressure- DAP) were assessed before (T0) and every day for the entire administration (T1-T14). Blood samples were collected for the evaluation of complete hemogram, Leukocyte subpopulation identification and counting and leukocyte differentiation antigens CD4 and CD8 at the day before the administration (T0) and every 7 days (T7 and T14). A reduction of HCPS pain scale scores and the number of WBC, monocytes and neutrophils and CD8 was observed with both CBDA and CBG/CBD treatment. No statistical differences were found in the physiological parameters. No subject required rescue analgesia or showed any adverse effects. The results of this study showed that oral administration of both CBDA and CBG/CBD oil may promote pain reduction in adult horses affected by chronic OA.